“You Just Don’t See Enough Normal” : Critical Perspectives on Infant-Feeding Discourse and Practice - Koerber, Amy (Journal of Business and Technical Communication, 2005)
Building on Herndl’s concept of critical practice, this article presents a case study of attempts to change the discourse practices surrounding breast-feeding in today’s medical environment. To complicate readers’ understanding of rhetorical agency, resistance, and discursive change, the author considers the rhetorical efforts of two high-profile physicians alongside those of the nonphysician breast-feeding advocates she interviewed. Ultimately, this dual perspective shows that discursive efforts to change medical practices can fail, even when supported by powerful figures within the medical establishment, if the new ideas communicated in such efforts conflict with long-established material conditions.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8xMDUwNjUxOTA1Mjc1NjM1